2013
DOI: 10.2340/16501977-1180
|View full text |Cite
|
Sign up to set email alerts
|

Step by step: A proof of concept study of C-Mill gait adaptability training in the chronic phase after stroke

Abstract: The concept of C-Mill gait adaptability training in the chronic phase after stroke is promising and warrants future research involving a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 37 publications
2
57
3
2
Order By: Relevance
“…A second component of the typical stabilization strategy is the modulation of mediolateral FP through active control of the swing limb. While in its early stages, gait training that includes practice stepping to targets may improve mobility by allowing more accurate FP [55]. …”
Section: Discussionmentioning
confidence: 99%
“…A second component of the typical stabilization strategy is the modulation of mediolateral FP through active control of the swing limb. While in its early stages, gait training that includes practice stepping to targets may improve mobility by allowing more accurate FP [55]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, walking adaptability is crucial when walking on uneven or cluttered terrains (unpredictable environment), to ensure safe and appropriate foot placement [64, 69]. Similarly, walking adaptability is essential when the task requires walking and turning to negotiate a curved path.…”
Section: Conceptual Challenges For the Measurement Of Walking Adapmentioning
confidence: 99%
“…Although both C-Mill therapy and the FALLS program incorporate practice of walking adaptability and thereby aim at improving community ambulation, and first results are encouraging in this regard [9, 14, 15], it is hypothesized that C-Mill therapy will result in better outcomes than the FALLS program, as a result of the expected greater amount of walking practice owing to treadmill training [18, 2022]. The results of the study of Moore et al [19] indeed showed significant gains in daily stepping and walking efficacy after treadmill training, compared with conventional physical therapy, which appears to be related to the number of steps taken per session.…”
Section: Discussionmentioning
confidence: 99%
“…The projected obstacles and stepping targets make C-Mill therapy well suited for task-specific and context-specific training because step adjustments are required to adapt to the projected context similar to the step adjustments required to adapt to environmental circumstances during community ambulation. A recent proof-of-concept study showed that C-Mill therapy in the chronic stage after stroke is not only well received by this population, but also beneficial [14]. C-Mill therapy resulted in training-related increments in walking speed and improvements in various other walking-related clinical scores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation